Nutrient restriction protects against valve interstitial cell calcification by upregulating ubiquitin mediated proteolysis - Phadwal, K.; Tang, Q.; Kurian, D.; Tan, X; Cawthorn, W. P.; MacRae, V. E. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCalcific aortic valve disease (CAVD) is a common and progressive valvular heart disease characterised by the pathological calcification of valve interstitial cells (VICs). Current clinical treatments, such as surgical valve replacement and transcatheter valve implantation, are invasive and do not target the underlying molecular mechanisms of calcification. Emerging evidence suggests that metabolic interventions may modulate cellular calcification processes. In this study, we investigated the potential of nutrient restriction (NR) as a non-invasive strategy to mitigate VIC calcification, with a particular focus on the role of the ubiquitin-proteasome system (UPS).MethodsPrimary rat valvular interstitial cells (RVICs) were cultured and subjected to in vitro calcification using calcium- and phosphate-enriched media. Nutrient restriction was induced by incubating cells in Hank's Balanced Salt Solution (HBSS). Calcification was assessed by quantifying calcium deposition and osteogenic marker expression. To explore the underlying molecular changes, a stable isotope labelling by amino acids in cell culture (SILAC)-based proteomic analysis was performed. The role of the UPS was further examined using pharmacological inhibition with MG132 and siRNA-mediated knockdown of key UPS components, including Cullin-2 (Cul2) and Ubiquitin-conjugating enzyme E2 H (Ube2H).ResultsNutrient restriction significantly downregulated the expression of osteogenic markers and reduced calcium deposition in RVICs. SILAC-based proteomics revealed the upregulation of multiple components of the UPS in nutrient-restricted cells. Notably, Cul2 and Ube2H were identified as potential key mediators of the anti-calcification effects observed. Inhibition of the proteasome with MG132 exacerbated calcification, while knockdown of Cul2 using siRNA increased osteogenic marker expression and calcium deposition, indicating the essential role of Cul2 in modulating VIC calcification under nutrient-restricted conditions.ConclusionThis study demonstrates that nutrient restriction effectively attenuates VIC calcification through the modulation of the ubiquitin-proteasome system. The protective role of UPS components, particularly Cul2 and Ube2H, suggests that targeting this pathway could represent a novel therapeutic approach for the management of CAVD. These findings also raise the possibility of employing dietary or metabolic interventions as non-invasive strategies to prevent or delay valve calcification.